The breakthrough years : a new scientific framework for raising thriving teens - Galinsky, Ellen (Flatiron Books, 2024)
"Blending cutting-edge research with engaging storytelling, The Breakthrough Years offers readers a paradigm-shifting comprehensive understanding of adolescence. Almost every adolescent has said to parents, "You JUST don't understand." In The Breakthrough Years, child development expert Ellen Galinsky explains why that is so often true. Galinsky's seven-year inquiry into the adolescent brain and behavior, including conducting original studies-uniquely informed by the questions adolescents have about their own development-shows why our understanding of adolescence is out of step with the latest research-and how to correct it. She: Identifies Five Basic Needs-such as belonging, developing competence, and building an identity-and show how we can meet these needs in positive ways; Presents Five Life Skills that are developing rapidly during adolescence like setting goals and strategies, perspective taking, critical thinking, and taking on challenges and shows how we can promote them; Introduces Solutions Mindset and Shared Solutions, a problem-solving mindset and process that parents and others can use to help create solutions to their adolescent's challenging problems. Ellen Galinsky's paradigm-shifting book will help parents and those who work with teens to understand adolescence not as the "I hope we can get though these years" but as the breakthrough years that they truly can be"--